1972
DOI: 10.1001/archneur.1972.00490110062006
|View full text |Cite
|
Sign up to set email alerts
|

Creutzfeldt-Jakob Disease

Abstract: Background: The prevalence and characteristics of sleep-wake disturbances in sporadic Creutzfeldt-Jakob disease (sCJD) are poorly understood. Methods: Seven consecutive patients with definite sCJD underwent a systematic assessment of sleep-wake disturbances, including clinical history, video-polysomnography, and actigraphy. Extent and distribution of neurodegeneration was estimated by brain autopsy in six patients. Western blot analyses enabling classification and quantification of the protease-resistant isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Creutzfeldt-Jakob disease, a prion disorder of the central nervous system (CNS), is also characterized by a very specific EEG pattern, which consists of periodic, bilaterally synchronous wave forms. 49 The periodic discharges take the form of diphasic or triphasic sharp waves, which repeat regularly at a frequency close to one per second. There is a fairly close relationship between the periodic complexes and myoclonic jerks; the latter may occur a few milliseconds before or after the electrical event.…”
Section: Encephalitidesmentioning
confidence: 99%
“…Creutzfeldt-Jakob disease, a prion disorder of the central nervous system (CNS), is also characterized by a very specific EEG pattern, which consists of periodic, bilaterally synchronous wave forms. 49 The periodic discharges take the form of diphasic or triphasic sharp waves, which repeat regularly at a frequency close to one per second. There is a fairly close relationship between the periodic complexes and myoclonic jerks; the latter may occur a few milliseconds before or after the electrical event.…”
Section: Encephalitidesmentioning
confidence: 99%
“…It is interesting that there seem to be some remarkable differences in the EEG findings between T. H. 59yr M. these two subgroups of the syndrome (Table 1). In reviewing the EEG findings of previously reported cases of subacute spongiform encephalopathy (Gloor et al, 1968;Goldhammer et al, 1972;Burger et al, 1972), it is confirmed that theabovementionedcharacteristics of the periodic spontaneous discharges of the Creutzfeldt-Jakob syndrome are most marked in subacute spongiform encephalopathy. It is said that the periodic discharge is recorded in about one-half of cases with Creutzfeldt-Jakob syndrome verified by necropsy (May, 1968;Yuasa, 1969;Hamanaka et al, M. 0.…”
Section: Discussionmentioning
confidence: 58%
“…66yr M. 1970). However, in reports dealing only with subacute spongiform encephalopathy, almost all of the cases showed the periodic synchronous discharges (Goldhammer et al, 1972;Burger et al, 1972;Roos et al, 1973). It may well be said that subacute spongiform encephalopathy, which is regarded as the most clearly definable subtype of Creutzfeldt-Jakob syndrome clinically and neuropathologically (Matsuoka et al, 1970;Schlote, 1970), also has the most characteristic s ofperiodic EEG findings.…”
Section: Discussionmentioning
confidence: 99%
“…The main symptoms, course of illness, and MRI findings were typical of sporadic CJD, and the initial symptoms of visual signs and myoclonus and methionine homozygosity at codon 129 of the human prion protein gene in our patient are in agreement with the elucidated genotype–phenotype correlation [5] . Myoclonus occurs in approximately 90% of patients with CJD; it appears at a relatively advanced stage of CJD and disappears in the terminal stage [1,3] . Myoclonus in CJD can be classified as rhythmic or irregular and positive or negative [2,6] , and polygraphic study reveals that positive EMG bursts of periodic myoclonus are always time-locked with PSWCs [2,6] .…”
Section: Discussionmentioning
confidence: 99%
“…Periodic sharp wave complexes (PSWCs) on electroencephalography are characteristic of Creutzfeldt–Jakob disease (CJD) and are frequently associated with rhythmic myoclonic jerks which are time-locked to PSWCs [1–3] . Some patients with CJD also present dystonia during the course of the disease.…”
Section: Introductionmentioning
confidence: 99%